2020
DOI: 10.1111/cas.14552
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of target capture‐based panel sequencing in hematological malignancies: A multicenter feasibility study

Abstract: Although next‐generation sequencing‐based panel testing is well practiced in the field of cancer medicine for the identification of target molecules in solid tumors, the clinical utility and clinical issues surrounding panel testing in hematological malignancies have yet to be fully evaluated. We conducted a multicenter prospective clinical sequencing study to verify the feasibility of a panel test for hematological tumors, including acute myeloid leukemia, acute lymphoblastic leukemia, multiple myeloma, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Several reports demonstrated that 6% to 27% of patients fail to receive genome-matched therapy after panel testing because of declining performance status [6,7]. Futhermore, the average of 47 days for NGS results in this study seems to be longer, in compared to previous reports [6,10], while a 47-day delay is typical for clinical settings in Japan [12,13]. One of the reasons for the delay for returning results to patients might be due to the additional timeline of expert panel, which is usually held 3 weeks after sequencing in Japan.…”
Section: Plos Onecontrasting
confidence: 50%
See 1 more Smart Citation
“…Several reports demonstrated that 6% to 27% of patients fail to receive genome-matched therapy after panel testing because of declining performance status [6,7]. Futhermore, the average of 47 days for NGS results in this study seems to be longer, in compared to previous reports [6,10], while a 47-day delay is typical for clinical settings in Japan [12,13]. One of the reasons for the delay for returning results to patients might be due to the additional timeline of expert panel, which is usually held 3 weeks after sequencing in Japan.…”
Section: Plos Onecontrasting
confidence: 50%
“…In this context, the use of the NCC Oncopanel as well as the FoundationOne 1 CDx has been covered under Japan's national health insurance since June 2019. Thus, there have been few evaluations of the feasibility and utility of clinical sequencing in cancer treatment in Japan [11][12][13]. At our hospital, clinical sequencing has been introduced for cancer patients as an application of precision oncology.…”
Section: Introductionmentioning
confidence: 99%
“… 3 As increasingly recognized as clinically significant, DDX41 was more frequently added to tumor sequencing panels for identifying variants responsible for myeloid malignancies. 4 , 5 DDX41 is a versatile protein not only functioning as a DNA/RNA sensor in innate immunity but also involved in transcription by altering the splicing process. 6 Recently, DDX41 in zebrafish was reported to be a crucial gatekeeper of over-producing hematopoietic stem and progenitor cells, by inhibiting excessive R-loops and thus preventing an inflammatory cascade.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various NGS based myeloid neoplasm panels developed in-house and commercially have been integrated into routine clinical practice [10][11][12][13]. Panels developed inhouse can differ substantially between laboratories in many aspects including gene content, the analysis of genes in a panel, sequencing library preparation chemistry, sequencing platform, and variant types detected [14][15][16][17][18][19][20]. Among many others, amplicon-based commercial panels, e.g.…”
Section: Introductionmentioning
confidence: 99%